Influence of primary reference fuels on isobaric combustion in a heavy-duty optical diesel engine. (1st April 2023) - Panthi, Niraj; Goyal, Harsh; AlRamadan, Abdullah; Magnotti, Gaetano
Highlights: Multiple injection strategy helps to achieve stable isobaric combustion for different PRFs. Improved fuel–air mixing due to longer ignition delay results in lower soot emissions in PRF100. PRF50 shows optimized engine performance and emissions. PRF100 results in less symmetric flame distribution. Initial soot signals formed near the nozzle holes, impinge the bowl-wall and flow along it due to flame-wall interactions. Abstract: Previous studies on isobaric combustion achieved using n -heptane/diesel fuel have shown the potential for higher engine efficiency compared to conventional diesel combustion. This was due to the lower heat transfer losses thanks to the lower rate of heat release and in-cylinder temperature, along with exhaust losses when coupled with a split cycle concept. However, the close-coupled injections implemented in isobaric combustion led to spray-flame interactions resulting in higher soot emissions. Potential ways to reduce the soot emissions are either employing multiple injectors, which helps to avoid the spray-flame interaction, or, as investigated in this study, burning higher octane or low reactivity fuels to increase the pre-combustion mixing time. This study investigated the effect of fuels on isobaric combustion in both all-metal and optical configurations of a heavy-duty optical diesel engine. Isobaric combustion was achieved using multiple injections from a single central injector; the engine performance, exhaust emissions, particle size distributions, and in-cylinder flame and soot distributions have been compared for three different primary reference fuels (PRFs) i.e., PRF0 ( n -heptane), PRF50 (volumetric mixture of 50 % n -heptane and 50 % isooctane), and PRF100 (isooctane). High-speed combustion luminosity, OH* chemiluminescence, and planar laser-induced incandescence of soot (soot-PLII) have been performed at a fixed air-excess ratio and peak cylinder pressure for all three fuels. The results demonstrated that PRF100 being the least reactive fuel out of the three tested fuels led to longer ignition delay resulting in more premixed combustion. PRF100 resulted in 4 % higher gross indicated efficiency, 48.8 % lower heat transfer losses, 17.6 % lower exhaust losses, and 87.4 % lower soot emission than PRF0; however, isobaric combustion using PRF100 was difficult to achieve. PRF50 is a promising candidate for isobaric combustion with slightly lower gross indicated efficiency than PRF100 but lower uHC/CO/soot/NOx emissions. Overall, PDI of Soot-PLII indicates initial soot is formed near the nozzle holes, and grow along the flame direction, until they hit the bowl-wall and flow along it due to flame-wall interactions. The soot PDI values are comparatively lower as we move axially away from the top of the cylinder.